Adipogenesis associated Mth938 domain containing (AAMDC) protein expression is regulated by alternative polyadenylation and microRNAs. Issue 14 (4th June 2019) - Xiao, Rong; Li, Chengping; Wang, Chao; Cao, Yang; Zhang, Lichun; Guo, Yan; Xin, Youzhi; Zhang, Haiyan; Zhou, Guoli
Abstract : Abstract : The post‐transcriptional events regulating expression of the adipogenesis associated Mth938 domain containing (AAMDC) protein are poorly understood. Here, we find that AAMDC expresses three isoforms due to alternative polyadenylation (APA) and alternative splicing (AS). Luciferase assay revealed that expression of the two isoforms with short and long 3′UTRs is differentially controlled. Further analyses showed that the short isoform displays higher translation efficiency and that miR‐2428/664a reduces expression of the long isoform, indicating that APA‐mediated shortening of the AAMDC 3′UTR renders the short isoform insusceptible to miRNA‐mediated suppression due to loss of the binding sites for miR‐2428/664a. Finally, we demonstrate that the short AAMDC isoform promotes bovine preadipocyte differentiation. Collectively, our findings indicate that AAMDC is post‐transcriptionally regulated through APA and microRNAs.